Emulsificação de coletor para flotação de grafita - Mariana Batista Lobato (2020)
Pure graphite is a naturally hydrophobic mineral. Graphite flotation processes use hydrocarbon collectors, mainly kerosene and diesel oil. These compounds have low solubility and dispersion in the aqueous flotation system. This leads to a higher consumption of these reagents and, consequently, a portion of these oils is discarded through the foam, which could result in contamination of the aqueous effluents in the surroundings. Previous emulsion of the collector oils might increase the efficiency of these reagents in the flotation process, due to the dispersion and increase of oil droplets in the aqueous system. Thus, the study proposed to investigate the efficiency of a kerosene emulsion as a collector reagent for graphite flotation. From kerosene and the selection of the best performing emulsifier, polyethylene glycol monooleate, oil-in-water (O/W) emulsions were formulated and characterized in terms of stability and droplet size. To evaluate the efficiency of these emulsions, concentration studies were carried out by means of flotation tests with graphite ore samples, from Itapecerica, previously characterized. The use of emulsified kerosene as a collect reagent was compared to the use of non-emulsified kerosene and the effects of varying the dosage of emulsified collectors were analyzed. X-ray fluorescence spectrometry, X-ray diffraction technique and Scanning Electron Microscopy analyzes indicated that the graphite ore samples have chemical, mineralogical and morphological characteristics similar to those observed in the shale graphite deposits, of the “flake” type, in the Minas-Bahia province. The emulsion was kinetically stable for a period of time sufficient for use in the mining industry. Furthermore, the emulsification of kerosene resulted in greater efficiency of the graphite flotation process using a lower kerosene dosage compared to the non-emulsified collector. Concluded that the use of emulsified collectors has promising applicability for the graphitic ore industry due to the increased efficiency of the flotation process and for promoting a reduction in the use of oil as a collector reagent, ensuring greater sustainability for the process.